On the (k-β) Points of Musielak-Orlicz Sequence Spaces Equipped with the Orlicz Norm - ZUO Ming-xia; LIU Hong-jiao (Journal of Harbin University of Science and Technology)
MusielakOrlicz spaces is the generalization of classical Orlicz spaces In this paper, we investigated the problem of characterization of the (kβ) points in Musielak Orlicz sequence spaces equipped with the Orlicz norm Firstly, the definition of (kβ) point is introduced Afterward a criteria for (kβ) points in MusielakOrlicz sequence spaces equipped with the Orlicz norm was given, and then we got the equivalent condition for local property (kβ) of these spaces